1998
DOI: 10.3892/ijmm_00000059
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine/paracrine regulation of human endometrial stromal remodeling by laminin and type IV collagen

Abstract: Abstract. The biological roles of laminin and type IV collagen in human endometrial stromal tissues were investigated by the evaluation of the expression levels in human endometrial tissues using immunohistochemistry. In addition, normal human endometrial stromal cells were cultured in vitro on laminin-or type IV collagen-coated plates and subjected to cytological analyses. Cyclic production of laminin and type IV collagen were detected and the two productions were significantly increased in late proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…73,74 The presence of collagen IV in the stromal layer is expected as endometrial fibroblasts, like fibroblasts from many other tissues, produce collagen IV. 53 However, collagen IV immunostaining in the stromal layer was strongly visible only in the upper region of the co-culture, near the epithelial cells, and was faint in the deeper regions of the stroma (data not shown), suggesting that collagen IV in the pericellular region of the fibroblasts may derive primarily from interactions with epithelia. In normal human endometrium, collagen IV immunostaining is localized to the basement membrane except during hormone differentiation where decidual cells (stromal fibroblasts that undergo differentiation in response to hormones) secrete basement membrane proteins locally around themselves, including collagen IV and laminin.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…73,74 The presence of collagen IV in the stromal layer is expected as endometrial fibroblasts, like fibroblasts from many other tissues, produce collagen IV. 53 However, collagen IV immunostaining in the stromal layer was strongly visible only in the upper region of the co-culture, near the epithelial cells, and was faint in the deeper regions of the stroma (data not shown), suggesting that collagen IV in the pericellular region of the fibroblasts may derive primarily from interactions with epithelia. In normal human endometrium, collagen IV immunostaining is localized to the basement membrane except during hormone differentiation where decidual cells (stromal fibroblasts that undergo differentiation in response to hormones) secrete basement membrane proteins locally around themselves, including collagen IV and laminin.…”
Section: Resultsmentioning
confidence: 86%
“…Matrix-binding peptides were designed to capture fibronectin ( FN-binder , 0.25 mM) produced by endometrial stromal fibroblasts throughout the cycle 49,52 and both laminin and type IV collagen basement membrane proteins ( BM-binder , 0.25 mM) that are normally produced by the epithelium during all menstrual cycle stages and locally produced and accumulated in the pericellular region of hormonally responsive fibroblasts in the stroma. 49,52,53 …”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that menstrual cycledependent Fas-mediated apoptotic susceptibility of human endometrial epithelium may be regulated by ECM components in BM-like-S. Our recent study showed that laminin and COL-4 differentially regulated cell viability of normal human endometrial stromal cells (5). The Fas-stimulation of normal human endometrial stromal cells has been reported to stimulate cell viability (19) and interaction with COL-4 has been reported to protect lens epithelial cells from Fas-dependent apoptosis by stimulating the production of soluble survival factors (20).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, abnormal expression of these ECM components in the endometrium was reported in a patient with unexplained infertility (1). We recently demonstrated that laminin and COL-4 regulated normal human endometrial stromal remodeling in an autocrine/paracrine fashion during the menstrual cycle (5). Therefore, in this study, we further investigated the effects of laminin and COL-4 on endometrial epithelial remodeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation